METHODOLOGY FOR IMPROVING MECHANISMS FOR APPLYING INFORMATION TECHNOLOGIES IN THE PROFESSIONAL ACTIVITIES OF FUTURE TEACHERS - Nazarov I.U. (Web of Journals Publishing, 2023)
Modern education is faced with the need to integrate information technology into the professional activities of teachers. This requires the development of methods and approaches that promote more effective use of information technologies in the educational process. This article proposes to consider a methodology for improving the mechanisms for using information technologies in the professional activities of future teachers.
Keywords: information technology, professional activity, future teachers, education, teaching methods, technology integration, teacher training, quality of education, modern approaches, information environment.